Expressing stance in brand posts on Facebook: a cross-cultural investigation - Iman Hany Omar; Iman Mahfouz; Sameh Al Ansary; Nevine Sarwat (Insights into Language, Culture and Communication)
The research cross-culturally investigates the expression of stance in the Facebook posts of large multinational automobile corporations in two countries, namely Egypt and the United Kingdom. It seeks to identify the ways stance markers differ from one culture and language to another and interpret the possible influence of culture on these metadiscoursal choices. Accordingly, a contrastive analysis is performed in which the Arabic and English Facebook pages are compared. Data are collected over a period of 5.5 months yielding a corpus of 214 Facebook posts. In order to analyse and interpret the data, the study adopts Hyland’s (2005) interpersonal model of metadiscourse with a particular focus on the stance category and explores the possible influence of each culture on the interpersonal markers employed using the cultural dimensions proposed by Hofstede, Hofstede, and Minkov (2010). The results of the study show that stance markers are significantly more common on the Egyptian pages. However, no striking variations are found in the general distribution of the stance markers across the various categories. While some similarities in the choice of the stance markers can be associated with the promotional genre, the results also reveal some differences dictated by the context and core values of the cultures under investigation. Hence, the findings of the study demonstrate that both culture and genre are two essential aspects that cannot be ignored when studying interactional discourse. The study has profound implications for corporations both nationally and internationally with regard to building solidarity with potential consumers and managing their corporate image in computer-mediated communications since country-specific content enhances usability, accessibility, and interactivity.   Received: 03 April 2023 Accepted: 14 April 2023 Published: 20 April 2023